Evaluation and Possibility of Rehabilitation of Damaged War Buildings in Benghazi - Elfaituri, Sadek Beleid (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
This study aimed at assessing the war-damaged buildings in Benghazi and the possibility of rehabilitation by visualizing and modeling of damaged buildings in according to international codes and to further bringing this evaluation into analysis to establish knowledge that will help to understand the behaviors of damaged buildings and to decide whether they are capable for reconstruction or not. To achieve this aim, certain models have been evaluated by either visual inspection or modeling evaluations by using one of the structural analysis programs after measuring and defining the structural properties. This research study concluded with a set of conclusions and recommendations based on the evaluation study and the different case studies that represented a basis for preparing a strategy for reconstruction and enhancing the evaluation and rehabilitation strategies based on these recommendations. Keywords: Structural Evaluation, Damage Evaluation, Existing Structures, Damaged War Buildings, Rehabilitation.

ÖZ: Bu çalışma, Bingazi'deki savaşta hasar gören binaların değerlendirilmesini ve rehabilitasyon olasılığını tartışmaktadır. Bu çalışmanın temel amacı, hasarlı binaların uluslararası kodlara göre değerlendirilmesine ışık tutmak ve hasarlı binaların davranışlarını anlamamıza ve yeniden inşa edilebilir olup olmadığına karar vermemize yardımcı olacak bilgileri oluşturmaktır. Bu amaçlara ulaşmak için, yapısal özelliklerin ölçülüp tanımlanmasının ardından yapısal analiz programlarından biri kullanılarak görsel inceleme ve detaylı inceleme yoluyla veya bu modellerden biri kullanılarak belirli modeller değerlendirilmiştir. Bu çalışma, değerlendirme çalışmasına ve bu tavsiyelere dayalı olarak değerlendirme ve rehabilitasyon stratejilerinin yeniden yapılandırılması ve iyileştirilmesi için bir temel oluşturan farklı vaka çalışmalarına dayanan bir dizi sonuç ve öneri ile sonuçlanmıştır. Anahtar kelimeler: Yapısal Değerlendirme, Mevcut Yapılar, Hasarlı Yapılar, Hasarlı Savaş Binaları, Rehabilitasyon.
Master of Science in Civil Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2020. Supervisor: Assoc. Prof. Dr. Mahmood Hosseini.
Keywords: Civil Engineering; Dmagaed War Buildings--Buildings--Repair and reconstruction--Preservation; Buildings--Rehabilitation; Structural Evaluation; Damage Evaluation; Existing Structures; Damaged War Buildings; Rehabilitation